Study of Differences in Children Nutrition Status Aged 6-24 Months with Exclusive and Non-Exclusive Breastfeeding in Mattampa Bulu Village - H, Siti Ramadhani; Sari, Jelita Inayah; Rahmadhani, Rauly (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Background: Breast milk is the most ideal biological and physiological first food during the growth and development process due to the presence of protective and nutritional factors and also the needs of children according to their age and phase of growth and development. Methods: This study aims to determine differences in nutritional status based on BB/U and PB/U for children aged 6-24 months in Mattampa Bulu Village. This study used 47 samples which were measured for body weight and length then the mother filled out a questionnaire. Result: The results of the study using the Chi Square test showed that there was a significant difference between nutritional status based on body weight in children with exclusive and non-exclusive breastfeeding history with p < 0.05 (p = 0.011), but there was no difference in nutritional status based on PB/ U with p > 0.05 (p=0.913). Results: Based on the research, it may be concluded that children with exclusive breastfeeding have good nutritional status based on the indicators of BB/U and there is no difference in the incidence of stunting in children with a history of exclusive and non-exclusive breastfeeding